Exploring the impact of mental and work-related stress on sick leave among middle-aged women: observations from the population study of women in Gothenburg, Sweden - Kirsten Mehlig; Amanda von Below; Kristina Holmgren; Cecilia Björkelund; Lauren Lissner; Ingmarie Skoglund; Magnus Hakeberg; Dominique Hange (Taylor & Francis Group, 2024)
Objective To investigate whether mental and work-related stress predicts a one-year incidence of sick leave in a cohort of middle-aged working women.Design The 2016/17 survey was part of the Population Study of Women in Gothenburg, Sweden, with registry data information on sick leave during one year pre- and post-baseline.Subjects A cohort of women aged 38 and 50 in 2016/17 (n = 573; 68% participation), of which 504 women were gainfully employed and not on sick leave ± 2 weeks around baseline examination; 493 women had complete data on stress exposure.Methods We studied associations between self-assessed mental and work-related stress and incident sick leave of >14 days during the year following the baseline examination. We used multiple logistic regression, adjusting for age and previous sick leave, and additionally for sleep quality, well-being, and physical activity.Results Overall, 75 women (16%) experienced at least one period of sick leave after baseline. Permanent stress during the last five years almost tripled the risk for incident sick leave, OR = 2.8 (95% CI 1.2-6.3), independent of previous sick leave, OR = 2.3 (95% CI 1.3-4.2). Among 21 specific work-related problems, conflicts at work, OR = 2.2 (95% CI 1.3-3.6), and low decision latitude, OR = 1.7 (95% CI 1.0-2.9), were associated with incident sick leave. The association with conflicts at work remained upon further covariate adjustment.Conclusion Low decision latitude and conflicts at work are risk factors for incident sick leave among working women. The impact of conflicts at work, irrespective of own involvement, may indicate a specific vulnerability among women of interest for future interventions.